IN PHARMACEUTICALS ROLE AND PRACTICAL SIGNIFICANCE OF COMPUTER TECHNOLOGIES - Atahanov Sanjar Anvarovich (Bright Mind Publishing, 2025)
This scientific article provides a detailed analysis of the role and practical significance of computer technologies in the pharmaceutical sector in 2025. The article presents practical examples of the application of modern technologies in the pharmaceutical sector, such as artificial intelligence, in silico modeling, digital laboratories, IoT, 3D printed drugs, nanoinformatics , and cybersecurity, in Uzbekistan and Central Asia.
Keywords: pharmaceuticals, computer technologies, artificial intelligence, digitization, in silico, 3D printing, Uzbekistan, Central Asia.